Literatur Review: Peran Motivasi Belajar Terhadap Pencapaian Akademik Siswa - Siti Qur’aini Ilani; Indri Fauzizah; Afita Sulaiman; Merika Setiawati (CV. ITTC INDONESIA, 2025)
Learning motivation is a crucial non-cognitive factor influencing students’ academic achievement. This article aims to review the role of learning motivation in supporting students’ academic achievement through a literature review approach. The method used was a systematic literature review by analyzing national and international journal articles published between 2020 and 2025. Data were collected from reputable databases such as Google Scholar, Semantic Scholar, and Garuda Kemdikbud. The findings indicate that learning motivation, particularly intrinsic motivation, has a significant impact on students’ academic achievement by encouraging active engagement, persistence, and the use of effective learning strategies. Moreover, motivation and academic achievement demonstrate a reciprocal relationship in which high motivation enhances achievement, while academic success strengthens students’ self-confidence and motivation. This review also identifies various strategies to enhance learning motivation, including meaningful learning, supportive learning environments, and collaborative support from teachers, families, and peers. These findings highlight the importance of strengthening students’ learning motivation as a key strategy to improve academic achievement across educational levels.